Mapping the Punt Hill IOCG system using geophysical, geochemical and spectral methods - an integrated approach. Issue 1 (1st December 2016) - Fabris, Adrian; Katona, Laszlo; Reed, Gary; Keeping, Tim; Gordon, Georgina; Gouthas, George; Swain, Greg
Abstract : Integrated data sourced from drill core geochemistry, spectral logs, petrophysical logs from available holes and geophysical data in and around the Punt Hill Copper-Gold prospect was used to characterise and map an IOCG system and predict prospective areas using a multi-disciplinary approach. Mineral assemblages associated with copper mineralisation were identified from geochemical analysis and spectral logs; density ranges associated with favourable mineral assemblages were noted and density inversions were fitted to these ranges in an attempt to predict similar densities in untested parts of the study area. Mineral assemblages associated with both prograde- and retrograde-dominated assemblages were found to be associated with copper mineralisation at Punt Hill. Densities associated with the prograde mineralising event were generally higher than those associated with the retrograde mineralising event; both are higher than background density. This provided a basis for fitting the results of density inversions to the known data to map inferred prograde and retrograde alteration within the study area. Inversions were performed at both the regional and deposit scale and were used to identify as yet untested regions with density values that are consistent with known zones of mineralisation and therefore showing high potential for further copper mineralisation.